Local Wisdom-Based Storytelling for Volcanic Disaster Preparedness: A Quasi-Experimental Study Among Elementary Students in Ternate City - Rasdiyanah Muhlis; Fitriyanti N Idrus; Amira Bin Seh Abubakar (Jurnal Kesehatan Komunitas Indonesia, 2026)
Background: Indonesia's position within the Pacific Ring of Fire exposes it to frequent natural disasters, including volcanic eruptions. Mount Gamalama in Ternate City, North Maluku Province, is among the country's most active volcanoes, and its 2018 eruption caused significant damage to surrounding communities. Elementary school-age children constitute a particularly vulnerable group due to limited knowledge and preparedness. Objective: This study aimed to examine the effect of a local wisdom-based storytelling model on volcanic eruption disaster preparedness among elementary school students in disaster-prone areas of Ternate City. Methods: A quasi-experimental design using a non-equivalent control group pre-test–post-test approach was employed, involving 60 students selected through purposive sampling (30 per group). The intervention group received health education via local wisdom-based storytelling incorporating illustrated comic books, animated videos, and mini booklets, while the control group received conventional classroom lectures. Results: Dependent t-test results indicated statistically significant improvements in both knowledge (control: p = 0.014; intervention: p = 0.019) and attitude (control: p = 0.040; intervention: p = 0.006) within both groups following the intervention. Mann-Whitney analysis revealed no significant between-group difference in either knowledge (p = 0.680) or attitude (p = 0.318), suggesting comparable short-term effectiveness of both approaches. Conclusion: The local wisdom-based storytelling model is an effective and contextually appropriate strategy for improving disaster preparedness. It is recommended as a participatory disaster education approach in volcanic eruption-prone areas.